Peringkasan Teks Artikel Ilmiah Berbahasa Indonesia dengan Metode Pembobotan Kalimat - Desti Fatmalasari; Favorisen Rosyking Lumbanraja (Jurnal Pepadun, 2022)
Technology of document monitoring is used to save time in digging up important information on documents. Summarize is a process of shrinking text shorter but still retaining the information contained therein. This research discusses the commemoration of the text of journal scientific using sentence weighting methods in the form of TF-IDF and Similarity. The goal the system wants to achieve can be to summarize text by recognizing patterns on text documents in txt format files. The system was built using PHP as a programming language. The trial was conducted using UAT (User Acceptance Testing) to find out the response to the interpreted system, namely by the likers scale questionnaire by dividing 3 aspects of the assessment. From the results of data processing (quantitative) obtained a value of 82.6% for the appearance of the system, a value of 80.2% for the efficiency of sentences generated in the system summary, and a value of 83.7% for satisfaction in using an automatic texting system in scientific articles Indonesian. The results of testing and implementation of the automatic text alerting system are received with a relatively strong acceptance rate.